2018
DOI: 10.15294/ijcets.v6i1.22710
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Model Pembelajaran Kooperatif Handep Berpasangan Berdasarkan Kaidah Quantum Teaching

Abstract: This article describes the development of handep cooperative learning model consist of 3-4 members become pair handep cooperative learning model in the form of module and validated by experts and students who used it. The model of development used R2D2, that focused on the design and development stage. The draft of the model at the single-path prototype level validated by the learning expert and small group validation in context the of mathematics learning in secondary school, to get the model at alpha version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…The reason was that through ethno mathematics students could easily understand math problems because it was suitable with the environment and daily life. The results of Demitra & Sarjoko's research found that local culture was suitable for improving students' math skills [22].…”
Section: Discussionmentioning
confidence: 99%
“…The reason was that through ethno mathematics students could easily understand math problems because it was suitable with the environment and daily life. The results of Demitra & Sarjoko's research found that local culture was suitable for improving students' math skills [22].…”
Section: Discussionmentioning
confidence: 99%
“…Pedoman penilaian yang digunakan adalah menggunakan skala huruf, seperti terlihat pada Tabel 1 dan Tabel 2. Deskripsi hasil pembelajaran post-test siklus I secara Individu dalam kegiatan pelatihan P2M ini melalui proses belajar mengajar mengacu pada rencana pelaksanaan pembelajaran sesuai dengan langkah-langkah model pembelajaran quantum teaching yang telah disediakan (Sarjoko & Demitra, 2018). Untuk mengetahui hasil belajar peserta maka diakhir pembelajaran peserta diberikan sebanyak 21 soal pilihan ganda.…”
Section: Refleksi Hasil Penilaian Pre-test Dan Post-test Siklus I Dan...unclassified